Working with Insulin, Carbohydrates, Ketones and Exercise to Manage Diabetes (WICKED): evaluation of a self‐management course for young people with Type 1 diabetes. Issue 11 (4th August 2019) - Johnson, B.; Norman, P.; Sanders, T.; Elliott, J.; Whitehead, V.; Campbell, F.; Hammond, P.; Ajjan, R.; Heller, S.
Abstract: Aims: To evaluate a 5‐day self‐management education course for young people with Type 1 diabetes and assess its effects on knowledge, self‐efficacy, beliefs, distress, self‐management behaviours and HbA1c . Methods: This is an evaluation of a structured education course. Young people (aged 16–24 years) with Type 1 diabetes were recruited from three diabetes centres. In the first centre, participants completed self‐report measures of knowledge, self‐efficacy, positive and negative outcome expectancies, and hypoglycaemic worries at baseline ( n =47) and the end of the course ( n =42). In two additional centres, participants completed these and other measures assessing self‐management behaviours, cognitive adaptation to diabetes and diabetes distress at baseline ( n =32), the end of the course (n=27) and 3‐month follow‐up ( n = 27). HbA1c levels were recorded at baseline ( n =79), 6 months ( n =77) and 12 months ( n =65). Results: There were statistically significant increases in self‐report knowledge, self‐efficacy, positive outcome expectancies and self‐management behaviours, and a statistically significant decrease in negative outcome expectances, between baseline and the end of the course. There were also statistically significant increases in self‐report knowledge, self‐efficacy, self‐management behaviours and cognitive adaptation to diabetes between baseline and 3‐month follow‐up. Compared with baseline, HbA1c levels decreased by a mean (sd ) of 5.44 (19.93) mmol/mol (0.48%) at 6 months ( P =0.019), and by 5.98 (23.32) mmol/mol (0.54%) at 12 months ( P =0.043). Discussion: The results indicate the potential benefits of a self‐management course designed to address the developmental needs and challenges faced by young people with Type 1 diabetes. Further studies with larger numbers and appropriate controls are required to confirm these initial findings. What's new?: Self‐management courses have been established for children and adults with diabetes; however, these may not be appropriate for young people (aged 16–24 years) who face unique developmental challenges. The WICKED self‐management course seeks to improve young people's control of their diabetes through increasing knowledge, self‐efficacy and self‐management behaviours, while acknowledging their specific needs and challenges. The course was developed and delivered in Sheffield before being evaluated in two other centres with different models of transition care. The WICKED course was found to increase self‐report knowledge, self‐efficacy and self‐management behaviours. Statistically significant reductions in HbA1c were observed at 6‐ and 12‐month follow‐ups.